The thrombin-derived host defense peptide GKY25 inhibits endotoxin-induced responses through Interactions with lipopolysaccharide and macrophages/monocytes - Schmidtchen, Artur (2015)
Host defense peptides have recently gained much interest as novel anti-infectives owing to their ability to kill bacteria and simultaneously modulate host cell responses. The cationic host defense peptide GKY25 (GKYGFYTHVFRLKKWIQKVIDQFGE), derived from the C terminus of human thrombin, inhibits proinflammatory responses in vitro and in vivo, but the mode of action is unclear. In this study, we show that GKY25, apart from binding bacterial LPS, also interacts directly with monocytes and macrophages in vitro, ex vivo, and in vivo. Moreover, GKY25 inhibits TLR4- and TLR2-induced NF-κB activation in response to several microbe-derived agonists. Furthermore, GKY25 reduces LPS-induced phosphorylation of MAPKs p38α and JNK1/2/3. FACS and electron microscopy analyses showed that GKY25 interferes with TLR4/myeloid differentiation protein-2 dimerization. The results demonstrate a previously undisclosed activity of the host defense peptide GKY25, based on combined LPS and cell interactions leading to inhibition of TLR4 dimerization and subsequent reduction of NF-κB activity and proinflammatory cytokine production in monocytes and macrophages.